Communicative Competence Development in the Course of Vocational Training - N. S. Abolina; O. V. Akimova (Obrazovanie i Nauka)
The paper, devoted to the communicative competence development, regards it as the key element of professional competence. Modern specialists in any sphere of professional activity need the necessary information and communication skills (i.e. the ability to use the principles of busyness communication for planning and analysis, goal-setting, choosing strategies, understanding the partners’ intentions and modifying the communication ways). The author highlights the labor market requirements to communication skills of the higher school graduates, and insists on introducing the theoretical and practical methods of communication competence development into the educational curricula. The paper specifies the aspects of perception and reflection in interpersonal contacts, and describes the group training methods with the main emphasis on such collective forms as role plays, group discussions, and training sessions. The outlines of the training program in business communication are given along with its approbation results including the improvements in students’ self-assessment, group communication, feelings, moods, activity, self-control in conflict situations, etc.